2020
DOI: 10.12973/ijem.6.1.223
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Faculty and Graduate Students’ Perceptions of Engaging Online Courses: A Mixed-Method Study

Abstract: The purpose of this study was to compare and contrast faculty and graduate students' perceptions of engaging online courses. This mixed-methods study occurred in a mid-sized state university in northeastern United States. Data from an online survey and semi-structured interviews indicated that graduate students and faculty perceived similar online course elements in the areas of social and teaching presence as engaging: interpersonal connections, structured learning environments, and variety in course activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The undesirable preconceived notions about online education commonly held by faculty must be modified or corrected to improve the views of faculty about teaching online and thereby potentially decrease their resistance to the adoption of online education [26]. Additionally, it must be remembered that the faculty's feeling of engagement in online courses was found to be related to both social and teaching presence [27]. There are certain dynamics that work well in face-to-face instruction but do not in online learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The undesirable preconceived notions about online education commonly held by faculty must be modified or corrected to improve the views of faculty about teaching online and thereby potentially decrease their resistance to the adoption of online education [26]. Additionally, it must be remembered that the faculty's feeling of engagement in online courses was found to be related to both social and teaching presence [27]. There are certain dynamics that work well in face-to-face instruction but do not in online learning.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized a descriptive, quantitative, cross-sectional research design. Twenty-seven (27) conveniently chosen faculty members in one State College in the Philippines responded to the online survey. This is more or less around 50% of the total sampled population (N=57) where the study was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of their critical comments about learning how to learn finally revealed that the current participants, though not as a whole, knew from experience how shared workload and expertise can accelerate task performance, and upgrade the quality of co-products, and why multiple modalities matter in meaning exchange, but at the same time, accepted the group structure as an enabling condition for such collective scaffolding. Even in most online learning environments, collaborative group work and classroom interaction could not be left out for the sake of student engagement and learning (Gonzalez & Moore, 2020). Our findings thus confirmed previous student reports of time-and effort-saving benefits, improvements in content, organisation, and grammaticality, and enhanced communication via multimodal meaning-making tools (Elola & Oskoz, 2010;Hanington et al, 2013;Kesli-Dollar & Tekiner-Tolu, 2015;Kim, 2018;Mulligan & Garofalo, 2011;Oskoz & Elola, 2014;Sepp & Bandi-Rao, 2015;Sevilla-Pavon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other researchers explored the potential reasons for the faculty preferences of face-to-face mode. Some studies concluded that faculty are usually more critical of online mode due to lack of human interface and presence of dummy students (Gonzalez and Moore, 2020;Dadhich et al, 2021;Wang, 2021). In contrast, some studies have shown that faculty favor online learning because of their inherent desire to update their digital skills and resume (Myers et al, 2004;Malay et al, 2022).…”
Section: Tutors' Preference For Online Versus Face-to-face Pbl Tutorialsmentioning
confidence: 99%